Thionated naphthalene diimides: tuneable chromophores for applications in photoactive dyads. Issue 2 (15th November 2017) - Pearce, Nicholas; Davies, E. Stephen; Horvath, Raphael; Pfeiffer, Constance R.; Sun, Xue-Zhong; Lewis, William; McMaster, Jonathan; George, Michael W.; Champness, Neil R.
Abstract : Thionation of naphthalene diimide and naphthalic imide phenothiazine dyads affords a systematic approach for tuning donor–acceptor energy gaps. Abstract : Varying the degree of thionation of a series of naphthalene diimide (NDI) and naphthalic imide (NI) phenothiazine dyad systems affords a systematic approach for tuning the system's donor–acceptor energy gap. Each dyad was compared to model NDI/NI systems and fully characterised through single crystal X-ray diffraction, NMR, cyclic voltammetry, electron paramagnetic resonance (EPR), transient absorption spectroscopy (TA), time-resolved infra-red spectroscopy (TRIR) and DFT. The measurements reveal that thionation increases both electron affinity of the NDI/NI acceptor dyad component and accessibility of the singly or doubly reduced states. Furthermore, FTIR and TA measurements show that excited state behaviour is greatly affected by thionation of the NDI and induces a decrease in the lifetime of the excited states formed upon the creation of charge-separated states.